2022
DOI: 10.5424/fs/2022313-19379
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting production in thinned clonal stands of Tectona grandis in Eastern Amazonia

Abstract: Aim of the study: We investigated the most suitable thinning ages and intensities to maximize productivity and minimize the rotation age of Tectona grandis clonal plantations in the Brazilian Eastern Amazon. Area of study: Capitão Poço, State of Pará, Eastern Amazonia, Brazil. Materials and methods: We used diameter, height, and volume data from 72 permanent plots measured on nine occasions. We determined the classification of forest sites using the generalized algebraic difference approach (GADA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is possible that the favorable environmental conditions and the genetic material (clonal material, which tends to be more productive) in our study provided an accelerated growth rate for teak trees in terms of biomass production, which had positive reflections on the productivity of wood with bark. This fact was confirmed in [31], in which it was suggested that the final harvest in clonal teak plantations in the Brazilian Amazon should be carried out between 13.9 and 16.6 years at the sites with the highest and lowest productive capacities, respectively.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is possible that the favorable environmental conditions and the genetic material (clonal material, which tends to be more productive) in our study provided an accelerated growth rate for teak trees in terms of biomass production, which had positive reflections on the productivity of wood with bark. This fact was confirmed in [31], in which it was suggested that the final harvest in clonal teak plantations in the Brazilian Amazon should be carried out between 13.9 and 16.6 years at the sites with the highest and lowest productive capacities, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…The seedlings were manually planted at the following spacings: 3.5 × 3.5 m, 3.75 × 3.75 m, and 4 × 4 m. For all stands, the following silvicultural techniques were performed using identical calendars: cleaning the area with a bulldozer, combating leaf-cutting ants with ant bait; liming with dolomitic limestone, applying 3 t ha −1 ; base fertilization, with application of 200 g plant −1 of NPK 8-28-16 and 100 g plant −1 of KCl, in the planting hole; weed control using crowning with the aid of a hoe, as well as mechanized and semi-mechanized weeding with a hydraulic tractor; coverage fertilization with application of 7 g plant −1 of boron and 100 g plant −1 of KCl; and artificial pruning with a saw and motor-pruner [30]. Systematic thinning was also performed at 4.5 (1st) and 8.5 (2nd) years, aiming to reduce the basal area by 50% for both thinning practices [30,31].…”
Section: Study Area and Silvicultural Practicesmentioning
confidence: 99%